Integrated hospital emergency care improves efficiency. (22nd January 2008) - Boyle, A A; Robinson, S M; Whitwell, D; Myers, S; Bennett, T J H; Hall, N; Haydock, S; Fritz, Z; Atkinson, P
Abstract : Background: There is uncertainty about the most efficient model of emergency care. An attempt has been made to improve the process of emergency care in one hospital by developing an integrated model. Methods: The medical admissions unit was relocated into the existing emergency department and came under the 4-hour target. Medical case records were redesigned to provide a common assessment document for all patients presenting as an emergency. Medical, surgical and paediatric short-stay wards were opened next to the emergency department. A clinical decision unit replaced the more traditional observation unit. The process of patient assessment was streamlined so that a patient requiring admission was fully clerked by the first attending doctor to a level suitable for registrar or consultant review. Patients were allocated directly to specialty on arrival. The effectiveness of this approach was measured with routine data over the same 3-month periods in 2005 and 2006. Results: There was a 16.3% decrease in emergency medical admissions and a 3.9% decrease in emergency surgical admissions. The median length of stay for emergency medical patients was reduced from 7 to 5 days. The efficiency of the elective surgical services was also improved. Performance against the 4-hour target declined but was still acceptable. The number of bed days for admitted surgical and medical cases rose slightly. There was an increase in the number of medical outliers on surgical wards, a reduction in the number of incident forms and formal complaints and a reduction in income for the hospital. Conclusions: Integrated emergency care has the ability to use spare capacity within emergency care. It offers significant advantages beyond the emergency department. However, improved efficiency in processing emergency patients placed the hospital at a financial disadvantage.